Comparative effects of green and black tea extracts on lowering serum uric acid in hyperuricemic mice - Chuang Zhu; Ling-Ling Tai; Xiao-chun Wan; Da-xiang Li; Yong-Qing Zhao; Yan Xu (Taylor & Francis Group, 2017)
Context: Tea (Camellia sinensis (L.) Kuntze [Theaceae]) is used to induce urination and inducing nervous excitation. Green and black teas have multifarious physiological functions. The different effects of green and black tea aqueous extracts (GTEs and BTEs) on hyperuricemia are not definitely reported. Objective: The different effects of GTEs and BTEs on lowering serum uric acid (UA) in hyperuricemic mice were determined. Materials and methods: Kunming mice were divided into nine groups (n = 6/each group). GTEs and BTEs at the doses of 0.5, 1 and 2 g/kg were orally administrated to mice for seven days, respectively. Hepatic xanthine oxidase (XOD) and adenosine deaminase (ADA) activities as mechanisms of actions were assessed. Results: Research indicated that the LD50 of tea extract is greater than 2 g/kg in mice. UA levels were suppressed significantly with dose-dependent treatment of 0.5, 1 and 2 g/kg BTEs (up to 25.5%, 28.7% and 29.8%, respectively); the serum UA levels were decreased by GTEs but not significant. The activities of XOD and ADA in high dose (2 g/kg) groups of both GTEs and BTEs were notably lower than those of the model group. Discussion and conclusions: The results suggested that both GTEs and BTEs have hypouricaemic and renal protective effects on hyperuricemic mice and the latter one was better. Our study sheds light on the research and development of anti-hyperuricemic functional foods and drugs from tea.